A mineral-based sorbent for rapid removal of radioactive metals and a method for its preparation

Through the coordinated design of clay mineral structure and surface engineering, porous silicate composite materials were prepared, which solved the problem of low efficiency and slow rate of existing adsorption materials, achieved efficient, rapid and low-cost removal of radioactive metal ions, and expanded resource utilization methods.

CN120437972BActive Publication Date: 2025-10-21鄂尔多斯市环保投资有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510905085.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-02
Publication Date
2025-10-21
Estimated Expiration
2045-07-02

AI Technical Summary

Technical Problem

Existing adsorption materials have low efficiency and slow rate in adsorbing radioactive metal ions, and have problems such as high cost and environmental unfriendliness, making it difficult to meet environmental protection standards.

Method used

A synergistic strategy of clay mineral structure engineering and surface engineering is adopted to transform natural clay and coal gangue into porous silicate composite materials. The affinity for metal ions is enhanced by introducing organic molecules to form an organic-inorganic composite structure.

Benefits of technology

It achieves efficient and rapid adsorption of radioactive metal ions, has low material cost and is environmentally friendly, is suitable for pollutant removal in different types of water bodies, and expands the utilization of clay minerals and coal gangue resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120437972B_ABST
    Figure CN120437972B_ABST
Patent Text Reader

Abstract

The application discloses a mineral-based adsorbent for quickly removing radioactive metals and a preparation method thereof, and belongs to the technical field of deep processing of natural non-metallic minerals and preparation of mineral functional adsorption materials. The preparation method is as follows: S1, natural clay ore powder and coal gangue powder are uniformly mixed, and then mixed with calcium compounds and magnesium compounds and ball milled; S2, boron compounds are added, and the material is uniformly mixed by continuously ball milling; S3, 10%-15% of water in mass percentage is added, and the material is treated by roll extrusion to form a sheet-shaped product; S4, the sheet-shaped product is calcined at 300-700 DEG C for 0.5-4h, cooled, and crushed; and S5, a modifier is sprayed, the product is sealed and placed for 6-24h, dried, and crushed to obtain the adsorbent. The natural clay and the coal gangue are used as raw materials, and the organic-inorganic composite adsorption material is prepared by combining a solid phase reaction with surface gas phase deposition modification, so that the radioactive metal ions can be quickly removed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a mineral-based adsorbent for rapidly removing radioactive metals and a preparation method thereof, belonging to the technical field of deep processing of natural non-metallic minerals and preparation of radioactive metal adsorption materials. Background Art

[0002] As energy and environmental crises intensify, the development of nuclear power is drawing increasing attention. The number of nuclear power plants worldwide continues to increase, and the nuclear industry is rapidly developing. The resulting release of radioactive metal ions (such as uranium, cesium, and strontium) poses a serious environmental threat, threatening human survival and development. These radioactive substances have extremely long half-lives and are highly toxic. Once they enter the environment, particularly water bodies, they can cause irreversible harm to natural ecosystems and human health. In recent years, large areas of the ocean have become unsafe due to contamination from nuclear wastewater discharges. Residual radionuclide contaminants in aquatic products pose a global threat to human survival and health. Therefore, there is an urgent need to develop new materials and methods for the rapid removal of radioactive metals from water. Traditional physicochemical treatment methods, such as precipitation, ion exchange, and membrane separation, are associated with low efficiency, high cost, and secondary pollution in removing radioactive heavy metal ions, making them difficult to meet increasingly stringent environmental standards.

[0003] In recent years, researchers have been committed to developing new and efficient adsorption materials to solve the above problems. The adsorption process can completely remove radioactive metals from water without causing secondary pollution. At the same time, the adsorption process is simple to operate and does not involve energy consumption. Although a large number of adsorption materials have been developed, most materials have problems such as high cost, low adsorption efficiency for low-concentration metals, and the material itself is not environmentally friendly. For this reason, the development of cost-effective adsorption materials using natural raw materials has become a hot topic in the industry. Among them, porous silicate materials derived from natural clay minerals have received more attention due to their unique structural properties. This type of material has rich pore structure, large specific surface area, good chemical stability and controllable surface properties, making it an ideal adsorbent candidate material. In addition, silicate materials themselves are non-toxic, widely available and inexpensive, with significant economic advantages.

[0004] However, natural clay and adsorption materials prepared by surface modification still face challenges in practical applications, such as low adsorption efficiency, slow adsorption rate, and upper limits to performance improvement. In order to improve its adsorption performance for radioactive metal ions, researchers have tried to optimize it through various modification methods, including but not limited to doping with metal oxides, introducing organic functional groups, and composite nanomaterials. Although these improvement measures can enhance the adsorption capacity of the material, their use in modification is limited to the mineral surface, and only increases adsorption sites on the surface to improve adsorption performance. Therefore, there is an upper limit to the performance of the prepared adsorption material, especially the adsorption rate needs to be further improved. Summary of the Invention

[0005] To address these technical issues, the present invention proposes a novel strategy of "synergistic clay mineral structural engineering and surface engineering." In terms of structural engineering, various inert minerals in the clay are converted and reconstituted into silicates, while carbon from coal gangue is used as a porogen to create a porous structure. In terms of surface engineering, organic molecules with a stronger affinity for metal ions are introduced onto the surface, forming an organic-inorganic composite structure. This results in a novel adsorbent material capable of efficiently and rapidly adsorbing radioactive metals. This material also retains the low cost and environmentally friendly advantages of clay minerals, making it a novel, environmentally friendly, green material.

[0006] Specifically, the present invention proposes a mineral-based adsorbent for rapidly removing radioactive metals and a preparation method thereof. The purpose is to convert natural clay and coal gangue, which are abundant in nature and low in cost, into environmentally friendly adsorbents with high-efficiency adsorption and removal capabilities for radioactive metal ions, thereby achieving efficient removal of radioactive heavy metal pollutants in different types of water bodies. On the one hand, this solves the problem of radioactive metal pollution, and on the other hand, it opens up new avenues for the high-value utilization of clay minerals and coal gangue resources, which are abundant in nature.

[0007] Metal ion adsorbents are materials that adsorb and remove toxic and harmful radioactive metal elements, and they hold promising applications in environmental protection, the nuclear industry, and other fields. Numerous types of radioactive metal adsorbents exist. Existing adsorbents, such as activated carbon and zeolites, have low adsorption capacities for radioactive metal ions and slow adsorption rates, making rapid and efficient removal difficult. In contrast, clay-based silicate composites offer inexpensive, readily available raw materials, simple preparation methods, and an environmentally friendly production process. They also possess excellent adsorption performance and offer a highly cost-effective solution. To address the shortcomings of existing radioactive metal adsorbents, the inventors, combined with theoretical research on adsorption driving force (the primary driving force for high-concentration heavy metal adsorption) and adsorption mass transfer efficiency (the primary driving force for deep adsorption of low-concentration heavy metals), have designed and developed a silicate-borate composite adsorbent derived from clay minerals and coal gangue. This composite material exhibits exceptionally high adsorption and purification capabilities for common radioactive metal ions, including uranium-235, nickel-63, cesium-135, cobalt-58, cadmium-113m, silver-110m, and strontium-90. It offers superior cost-effectiveness and a promising market outlook.

[0008] The details are as follows:

[0009] A method for preparing a mineral-based adsorbent for rapidly removing radioactive metals comprises the following steps:

[0010] S1. Natural clay mineral powder and coal gangue powder are uniformly mixed, and then mixed with a calcium compound and a magnesium compound, and ball-milled for 5-30 minutes to obtain a ball-milled material with a particle size of less than 76 μm;

[0011] S2. Add the boron compound to the ball-milled material and continue ball-milling for 10-60 min to mix the material evenly to obtain a ball-milled mixed material;

[0012] S3, adding 10%-15% by mass of water to the ball milled mixed material, and then performing a double-roll extrusion process to form a sheet product;

[0013] S4, calcining the flaky product at 300-700°C for 0.5-4h, then cooling and pulverizing to obtain a powder;

[0014] S5. Spray a modifier into the powder, place it in a sealed container for 6-24 hours, and then dry and crush it to obtain a mineral-based adsorbent that can quickly remove radioactive metals.

[0015] Furthermore, in step S1, the amount of the calcium compound and the magnesium compound is 25%-150% of the total mass of the clay mineral powder and the coal gangue powder, the amount of the magnesium compound is 10%-60% of the total mass of the calcium compound and the magnesium compound, and the amount of the coal gangue powder is 5%-30% of the total mass of the clay mineral and the coal gangue powder;

[0016] The natural clay mineral powder includes one or more of attapulgite, illite, chlorite, montmorillonite, illite-montmorillonite, kaolinite, talc, quartz, calcite, amorphous hematite, feldspar, and mica; the mass fraction of carbon element in the coal gangue powder is 8%-15%.

[0017] Furthermore, the calcium compound is at least one of calcium oxide, calcium hydroxide, calcium sulfate, calcium chloride, calcium carbonate, and calcium citrate; and the magnesium compound is at least one of magnesium oxide, magnesium hydroxide, magnesium sulfate, magnesium chloride, magnesium carbonate, and magnesium citrate.

[0018] Furthermore, in step S2, the amount of the boron compound is 30%-120% of the mass of the clay;

[0019] The boron compound is at least one of boric acid, sodium tetraborate and sodium metaborate.

[0020] Furthermore, in step S4, during calcination, the heating rate is 5-20°C / min.

[0021] Furthermore, in step S5, the modifier is one of citric acid, creatine, nitrilotriacetic acid, and ethylenediaminetetraacetic acid, and the amount of the modifier is 0.5%-2% of the total mass of the clay mineral powder and coal gangue.

[0022] In a second aspect, the present invention provides an adsorbent prepared by a method for preparing a mineral-based adsorbent for rapidly removing radioactive metals. The adsorbent is a porous silicate composite material containing silicon, magnesium, aluminum, boron, calcium, and iron elements, and exists in the form of a composite of magnesium, aluminum, or iron silicate and calcium borate.

[0023] Furthermore, the adsorbent is a porous silicate composite material with high adsorption capacity and fast adsorption rate, which is obtained by mineral transformation and reconstruction of natural clay minerals and coal gangue under the action of borates, calcium salts, and magnesium salts. The carbon components in the coal gangue are then decomposed at high temperature to produce pores and surface organic functional groups, which significantly improve the adsorption capacity and adsorption rate. The principle is as follows:

[0024] During calcination, boron compounds react with aluminosilicate minerals in natural clay in a solid-state reaction, forming new phases such as calcium borate. This, in turn, destroys the clay's original inert structure, forming a more active silicate-borate complex. Calcium and magnesium compounds act as mineralizers, promoting the decomposition and recombination of minerals like quartz and calcite in the clay, forming an active framework rich in Mg / Al / Fe silicates. The 8%-15% carbon in the gangue oxidizes and decomposes during calcination, producing CO2 gas that forms a mesoporous-microporous composite structure. This increases the specific surface area from 56.08 m² / g in natural clay to 491.89 m² / g, significantly increasing the number of adsorption sites.

[0025] Simultaneously, carboxyl (-COOH)-containing modifiers such as citric acid and EDTA bond to the Si-O-groups on the silicate surface through spray deposition, forming an organic-inorganic hybrid interface that enhances the complexing capacity for metal ions. The porous structure and surface hydrophilic groups synergistically accelerate the diffusion of metal ions to internal active sites, achieving 90% of the equilibrium adsorption capacity within 10 minutes.

[0026] In a third aspect, the present invention provides an application of an adsorbent for removing radioactive metal ions in wastewater.

[0027] Furthermore, the radioactive metal ion is UO2 2+ , Cd(II), Ag(I), Co(II), Ni(II), Cs(I), Sr(II).

[0028] Furthermore, the adsorbent removes metal ions at a concentration of 1-50 mg / L.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. The present invention adopts a "clay mineral structural engineering and surface engineering synergy" approach. In terms of structural engineering design, various inert minerals in the clay are converted and reconstructed into silicates, while the carbon in the coal gangue is used as a porogen to form a porous structure. In terms of surface engineering design, organic molecules with stronger affinity for metal ions are introduced to the surface to form an organic-inorganic composite structure, resulting in a new adsorption material that can efficiently and rapidly adsorb radioactive metals. The prepared new adsorption material also maintains the low cost and environmentally friendly advantages of clay minerals, and is a new environmentally friendly green material.

[0031] 2. The present invention proposes a mineral-based adsorbent for rapid removal of radioactive metals and a preparation method thereof, the purpose of which is to convert natural clay (attapulgite clay) and coal gangue, which are abundant in nature and low in cost, into environmentally friendly adsorbents with high-efficiency adsorption and removal capabilities for radioactive metal ions, thereby achieving high-efficiency removal of radioactive heavy metal pollutants in different types of water bodies. On the one hand, it solves the problem of radioactive metal pollution, and on the other hand, it opens up a new way for the high-value utilization of clay minerals and coal gangue resources that are abundant in nature. Metal ion adsorbents are materials that adsorb and remove toxic and harmful radioactive metal elements, and have broad application prospects in the fields of environmental protection and nuclear industry. There are many types of radioactive metal adsorbents. Existing adsorption materials such as activated carbon and zeolites have low adsorption capacity for radioactive metal ions and slow adsorption rates, making it difficult to achieve The goal is to remove radioactive metals quickly and efficiently. In comparison, the raw materials of clay-based silicate composite materials are cheap and easy to obtain, the preparation method is simple, the production process is green and environmentally friendly, and the adsorption performance is excellent, with a very high cost performance. In response to the shortcomings of current radioactive metal adsorption materials, the present invention combines theoretical research on adsorption driving force (the main driving force for the adsorption of high-concentration heavy metals) and adsorption mass transfer efficiency (the main driving force for the deep adsorption of low-concentration heavy metals), and designs and prepares a preparation technology for silicate-borate composite adsorption materials derived from clay minerals and coal gangue (the adsorbent of the present invention). It has ultra-high adsorption and purification capabilities for common radioactive metal ions including uranium-235, nickel-63, cesium-135, cobalt-58, cadmium-113m, silver-110m, strontium-90, etc., and is more advantageous in terms of cost performance, with broad market prospects.

[0032] 3. Under the induction of boron compounds, calcium compounds and magnesium compounds, the present invention realizes the structural transformation of minerals in natural clay and coal gangue and their in-situ composite with calcium borate salts, and at the same time produces a large number of active Si-O-groups on the surface of the material, thereby enhancing the chemical complexation, electrostatic adsorption and ion exchange capabilities of the adsorption material for heavy metals; at the same time, the carbon in the coal gangue can act as a "porogen" in the material formation process, so that the obtained adsorbent has a better pore structure and a larger specific surface area, which is conducive to the simultaneous increase of the adsorption driving force and mass transfer efficiency, and achieves the goal of efficient and rapid removal of metal ions. The target product can achieve complete adsorption of metal ions within 10 minutes.

[0033] 4. The pore size of the adsorbent provided by the present invention is mainly distributed in the range of 2-50 nm, which proves that there are mainly micropores and mesopores. As can be seen from Table 1, the specific surface area of ​​natural clay is 56.08 m 2 / g, the specific surface area of ​​coal gangue is 12.31 m 2 / g, while the specific surface area of ​​adsorbent RMA-1 increased to 491.89 m 2 / g (8.77 times the specific surface area of ​​natural clay and 39.96 times the specific surface area of ​​coal gangue), which is more conducive to the rapid diffusion of metal ions to the adsorption sites inside the adsorbent and improves the adsorption rate.

[0034] 5. The adsorbent provided by the present invention has a much higher adsorption capacity for Co(II) and Ni(II) than other adsorbents (commercial activated carbon and commercial zeolite) at any time period, reaching 232 mg / g and 186 mg / g, respectively, which is significantly higher than the adsorption capacity of commercial activated carbon and zeolite (<50 mg / g). In addition, the adsorption rate of RMA-1 adsorbent is faster than that of other adsorbents, reaching more than 90% of the equilibrium adsorption in 10 minutes. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, without paying any creative work, other related drawings can be obtained based on these drawings, which also fall within the scope of protection of the present application.

[0036] Figure 1 XRD curves of natural clay and adsorbent RMA-1 prepared by the technology of the present invention;

[0037] Figure 2 The infrared spectra of natural clay and the adsorbent RMA-1 prepared by the technology of the present invention;

[0038] Figure 3 SEM images of natural clay (a) and adsorbent RMA-1 (b) prepared by the technology of the present invention;

[0039] Figure 4 Nitrogen adsorption-desorption isotherm (a) and pore size distribution curve (b) of the adsorbent RMA-1 prepared by the technology of the present invention;

[0040] Figure 5 The adsorption kinetic curves of radioactive metal ions Ni and Co by the adsorbent RMA-1 prepared by the technology of the present invention and commercial activated carbon and zeolite; DETAILED DESCRIPTION

[0041] Below in conjunction with embodiment, technical solution of the present invention is further described, and these embodiments should not be construed as limiting the technical solution. In order to make the purpose, technical solution and advantages of the present application embodiment clearer, the technical solution in the present application embodiment will be clearly and completely described below. In the embodiment, if specific conditions are not specified, it is carried out according to the conditions recommended by normal conditions or manufacturers. If the manufacturer is not specified for reagents used or instruments, they are all conventional products that can be purchased for commercial use.

[0042] Example 1

[0043] 80 kg of natural clay mineral powder (produced in Hangjin Banner, Ordos City, Inner Mongolia Autonomous Region, primarily containing attapulgite, illite, chlorite, quartz, calcite, and amorphous hematite) and 20 kg of coal gangue (15% carbon content) powder were mixed uniformly. 67.5 kg of calcium hydroxide and 7.5 kg of magnesium hydroxide were then added and ball-milled for 5 minutes. 50 kg of sodium metaborate was added to the milled material, and ball milling continued for 60 minutes to ensure thorough mixing and solid-phase reaction. 15 kg of water was added to the milled material, and the mixture was then double-roll extruded to form a flaky product. The flaky product was calcined at 700°C for 0.5 h at a heating rate of 10°C / min, cooled, and pulverized to obtain a powder. An aqueous solution containing 2 kg of citric acid was sprayed into the calcined product (the amount of water was controlled to ensure complete dissolution and uniform spraying), and the product was placed in a sealed container for 24 hours to ensure sufficient modification. The product was then dried and crushed to obtain an organic-inorganic composite radioactive metal ion adsorbent containing carboxyl functional groups, named RMA-1.

[0044] Example 2

[0045] 95 kg of natural clay mineral powder (produced in Hangjin Banner, Ordos City, Inner Mongolia Autonomous Region, primarily containing attapulgite, illite, chlorite, quartz, calcite, and amorphous hematite) and 5 kg of coal gangue powder (8% carbon content) were mixed uniformly. 20 kg of calcium oxide and 5 kg of magnesium sulfate were then added and ball-milled for 30 minutes. 30 kg of sodium tetraborate was added to the milled material, and ball milling continued for 10 minutes to ensure thorough mixing and solid-phase reaction. 10 kg of water was added to the milled material, and the mixture was then double-roll extruded to form a flaky product. The flaky product was calcined at 500°C for 0.5 h at a heating rate of 5°C / min, cooled, and pulverized to obtain a powder. An aqueous solution containing 0.5 kg of creatine was sprayed into the calcined product (the amount of water was controlled to ensure complete dissolution and uniform spraying), and the product was placed in a sealed container for 6 hours to ensure sufficient modification. It was then dried and crushed to obtain an organic-inorganic composite radioactive metal ion adsorbent containing carboxyl functional groups, named RMA-2.

[0046] Example 3

[0047] 70 kg of natural clay powder (produced in Hangjin Banner, Ordos City, Inner Mongolia Autonomous Region, primarily containing attapulgite, illite, chlorite, quartz, calcite, and amorphous hematite) and 30 kg of coal gangue powder (10% carbon content) were mixed uniformly. 90 kg of calcium carbonate and 10 kg of magnesium oxide were then added and ball-milled for 20 minutes. 80 kg of boric acid was added to the milled material, and the milling process continued for 30 minutes to ensure thorough mixing and solid-phase reaction. 12 kg of water was added to the milled material, and the mixture was then double-roll extruded to form a flaky product. The flaky product was calcined at 600°C for 4 hours at a heating rate of 20°C / min, cooled, and pulverized to obtain a powder. An aqueous solution containing 3 kg of ethylenediaminetetraacetic acid (the amount of water is controlled to ensure complete dissolution and uniform spraying) is sprayed into the calcined product, and the product is placed in a sealed container for 12 hours to ensure sufficient modification. The product is then dried and crushed to obtain an organic-inorganic composite radioactive metal ion adsorbent containing carboxyl functional groups, named RMA-3.

[0048] Example 4

[0049] 80 kg of natural clay mineral powder (produced in Hangjin Banner, Ordos City, Inner Mongolia Autonomous Region, primarily containing attapulgite, illite, chlorite, quartz, calcite, and amorphous hematite) and 20 kg of coal gangue powder (9% carbon content) were mixed uniformly. 60 kg of calcium chloride and 90 kg of magnesium hydroxide were then added and ball-milled for 10 minutes. 120 kg of sodium metaborate was added to the milled material, and ball milling continued for 30 minutes to ensure thorough mixing and solid-phase reaction. 13 kg of water was added to the milled material, and the mixture was then double-roll extruded to form a flaky product. The flaky product was calcined at 650°C for 2 hours at a heating rate of 15°C / min, cooled, and pulverized to obtain a powder. An aqueous solution containing 1 kg of nitrilotriacetic acid (the amount of water is controlled to ensure complete dissolution and uniform spraying) is sprayed into the calcined product, and the product is placed in a sealed container for 24 hours to ensure sufficient modification. The product is then dried and crushed to obtain an organic-inorganic composite radioactive metal ion adsorbent containing carboxyl functional groups, named RMA-4.

[0050] Example 5

[0051] 80 kg of natural clay powder (produced in Shangsi County, Guangxi, primarily containing illite, quartz, calcite, and amorphous hematite) and 20 kg of coal gangue powder were mixed uniformly. 67.5 kg of calcium oxide and 7.5 kg of magnesium carbonate were then added and ball-milled for 15 minutes. 35 kg of sodium tetraborate was added to the milled material, and ball milling continued for 50 minutes to ensure thorough mixing and solid-phase reaction. 15 kg of water was added to the milled material, and the mixture was then subjected to double-roll extrusion to form a flake product. The flake product was calcined at 700°C for 0.5 h at a heating rate of 20°C / min, cooled, and pulverized to obtain a powder. An aqueous solution containing 1 kg of ethylenediaminetetraacetic acid (the amount of water was controlled to ensure uniform spraying) was sprayed into the calcined product. The product was sealed and allowed to stand for 20 hours to ensure full modification. The product was then dried and pulverized to obtain an organic-inorganic composite radioactive metal ion adsorbent containing carboxyl functional groups, designated RMA-5.

[0052] Comparative Example 1

[0053] The main difference between this comparative example and Example 4 is that no calcium compound and magnesium compound are added, specifically as follows:

[0054] 80 kg of natural clay mineral powder (produced in Hangjin Banner, Ordos City, Inner Mongolia Autonomous Region, primarily containing attapulgite, illite, chlorite, quartz, calcite, and amorphous hematite) and 20 kg of coal gangue (15% carbon content) powder were mixed uniformly. 50 kg of sodium metaborate was then added and ball-milled for 60 minutes to ensure thorough mixing and solid-phase reaction. 15 kg of water was added to the milled mixture, followed by double-roll extrusion to form a flake product. The flake product was calcined at 700°C for 0.5 h at a heating rate of 10°C / min, cooled, and pulverized to obtain a powder. An aqueous solution containing 2 kg of citric acid (the amount of water was controlled to ensure uniform spraying) was sprayed into the calcined product. The product was sealed and stored for 24 hours to ensure full modification. The product was then dried and pulverized to obtain an organic-inorganic composite radioactive metal ion adsorbent containing carboxyl functional groups, designated CK-1.

[0055] Comparative Example 2

[0056] The main difference between this comparative example and Example 4 is that no borate is added, specifically as follows:

[0057] 80 kg of natural clay mineral powder (produced in Hangjin Banner, Ordos City, Inner Mongolia Autonomous Region, primarily containing attapulgite, illite, chlorite, quartz, calcite, and amorphous hematite) and 20 kg of coal gangue (15% carbon content) powder were mixed uniformly. 67.5 kg of calcium hydroxide and 7.5 kg of magnesium hydroxide were then added and ball-milled for 60 minutes to ensure thorough mixing and solid-phase reaction. 15 kg of water was added to the milled mixture, followed by double-roll extrusion to form a flake product. The flake product was calcined at 700°C for 0.5 h at a heating rate of 10°C / min, cooled, and pulverized to obtain a powder. An aqueous solution containing 2 kg of citric acid (the amount of water was controlled to ensure uniform spraying) was sprayed into the calcined product. The product was sealed and stored for 24 hours to ensure full modification. The mixture was then dried and pulverized to obtain an organic-inorganic composite radioactive metal ion adsorbent containing carboxyl functional groups, designated CK-2.

[0058] Experimental part

[0059] Experiment 1

[0060] The adsorbent RMA-1 prepared in Example 1 and the natural clay were subjected to X-ray powder diffraction (XRD) analysis. The results are as follows: Figure 1 As shown. Figure 1The natural clay sample clearly exhibits multiple distinct diffraction peaks, including characteristic peaks of quartz at 2θ = 20.87°, 26.68°, 36.55°, 40.40°, 42.46°, 50.13°, and 59.94°; characteristic peaks of calcite at 2θ = 29.40° and 35.97°; characteristic peaks of attapulgite at 2θ = 7.98°; and characteristic peak of illite at 2θ = 8.46°. However, in the spectrum of the adsorbent RMA-1, obtained after treatment using the technology described in this invention, these characteristic peaks of natural clay minerals are significantly weakened or even disappear. Instead, a new diffraction peak of calcium borate appears at 2θ = 29.86°. This phenomenon clearly demonstrates that, under the induction of boron compounds, calcium compounds, and magnesium compounds, most of the minerals in the clay undergo structural transformation and reorganization, forming a new silicate-borate complex.

[0061] Experiment 2

[0062] The infrared spectrum of the adsorbent RMA-1 prepared in Example 1 was analyzed. Figure 2 ,from Figure 2 It can be seen that the infrared spectrum of adsorbent RMA-1 shows the CH stretching vibration peak of organic matter (2924 cm -1 and 2852 cm -1 ), and the characteristic peak of the carboxylic acid group (1680 cm -1 ), which proves that there are carboxyl groups on the surface of adsorbent RMA-1 with strong complexing ability for metal ions.

[0063] Experiment 3

[0064] The surface morphology of the adsorbent RMA-1 prepared in Example 1 and the raw material natural clay powder in Example 1 was observed by scanning electron microscopy (SEM). Figure 3 ), a is natural clay, b is adsorbent RMA-1; Figure 3 It can be seen that rod-shaped, flaky and blocky mineral particles exist in natural clay, indicating that there are multiple minerals in the clay. After the process of the present invention, the disordered mineral particles are converted into relatively uniform porous silicates.

[0065] Experiment 4

[0066] The raw materials used in Example 1 (natural clay ore powder, coal gangue powder) and adsorbent RMA-1 were placed in an oven and dried at a suitable temperature to constant weight to remove moisture and other volatile substances. A certain amount of natural clay, coal gangue, and composite adsorbent RMA-1 samples were accurately weighed using an electronic balance and placed into sample tubes. The sample tubes containing the samples were mounted on a BET surface area analyzer for adsorption-desorption isotherm measurement. After the test, adsorption-desorption isotherm data were obtained from the BET surface area analyzer. The adsorption data was processed using the BET equation to calculate the specific surface area of ​​the sample. The pore size distribution of the sample was determined using the Barrett-Joiner-Halenda (BJH) method or other pore size distribution calculation methods.

[0067] The calculated pore structure parameters such as specific surface area, pore volume and average pore diameter are shown in Table 1, and the pore size distribution curve is shown in Figure 4 , Figure 4 Nitrogen adsorption-desorption isotherm (a) and pore size distribution curve (b) of the adsorbent RMA-1 prepared by the technology of the present invention; Table 1 shows the pore structure parameters of natural clay, coal gangue and the adsorbent RMA-1 prepared by the technology of the present invention.

[0068] from Figure 4 It can be seen that the pore size of the sample is mainly distributed in the range of 2-50 nm, which proves that there are mainly micropores and mesopores. As can be seen from Table 1, the specific surface area of ​​natural clay is 56.08 m 2 / g, the specific surface area of ​​coal gangue is 12.31 m 2 / g, while the specific surface area of ​​adsorbent RMA-1 increased to 491.89 m 2 / g (8.77 times the specific surface area of ​​natural clay and 39.96 times the specific surface area of ​​coal gangue), which is more conducive to the rapid diffusion of metal ions to the adsorption sites inside the adsorbent and improves the adsorption rate.

[0069] Table 1 Pore structure parameters of natural clay, coal gangue and adsorbent RMA-1 prepared by the technology of the present invention

[0070]

[0071] Experiment 5

[0072] A high concentration solution with a Co(II) and Ni(II) ion concentration of 200 mg / L was prepared. The RMA-1 adsorbent (particle size ≤76 μm), commercial activated carbon (particle size ≤76 μm), and commercial zeolite (particle size ≤76 μm) prepared in Example 1 were added to the above solution, respectively. The mixture was stirred or shaken for different times (2.5, 5, 10, 20, 30, and 60 min). The adsorbent was quickly filtered and separated at each time point. The concentration of metal ions in the filtrate was measured. The adsorption amount at each time point was calculated based on the difference in metal ion concentration in the solution before and after adsorption and the mass of the adsorbent. The results are shown in the attached figure. Figure 5 .

[0073] from Figure 5 As can be seen, the adsorption capacity of Co(II) and Ni(II) by RMA-1 is significantly greater than that of other adsorbents at all time periods, reaching 232 mg / g and 186 mg / g, respectively, significantly exceeding the adsorption capacity of commercial activated carbon and zeolite (<50 mg / g). Furthermore, RMA-1 exhibits a faster adsorption rate than other adsorbents, reaching over 90% of equilibrium adsorption within 10 minutes.

[0074] According to the above test method, the adsorbents CK-1 and CK-2 prepared in Comparative Examples 1 and 2, RMA-1 adsorbent, commercial activated carbon, and natural clay were evaluated for their effects on UO2 2+ , Cd(II), Ag(I), Co(II), Ni(II), Cs(I), and Sr(II), and the results are shown in Table 2. As can be seen from Table 2, the saturated adsorption capacity of the composite adsorbent RMA-1 prepared by the present invention for radioactive elements uranium (U), nickel (Ni), cesium (Cs), cobalt (Co), cadmium (Cd), silver (Ag), and strontium (Sr) ions is significantly higher than that of the comparative samples CK-1 and CK-2, and is also significantly higher than that of natural clay and commercial activated carbon.

[0075] Table 2 Saturated adsorption capacity of radioactive metal ions by clay and adsorbent

[0076]

Claims

1. A method for preparing a mineral-based adsorbent for rapid removal of radioactive metals, characterized in that: The following steps are involved: S1. Natural clay mineral powder and coal gangue powder are uniformly mixed, and then mixed with a calcium compound and a magnesium compound, and ball-milled for 5-30 minutes to obtain a ball-milled material; S2. Add the boron compound to the ball-milled material and continue ball-milling for 10-60 min to mix the material evenly to obtain a ball-milled mixed material; S3, adding 10%-15% by mass of water to the ball milled mixed material, and then performing a double-roll extrusion process to form a sheet product; S4, calcining the flaky product at 300-700°C for 0.5-4h, then cooling and pulverizing to obtain a powder; S5. Spray a modifier into the powder, place it in a sealed container for 6-24 hours, and then dry and crush it to obtain a mineral-based adsorbent for quickly removing radioactive metals; the modifier is one of citric acid, creatine, nitrilotriacetic acid, and ethylenediaminetetraacetic acid, and the amount of the modifier is 0.5%-2% of the total mass of the clay ore powder and coal gangue.

2. The method for preparing a mineral-based adsorbent for rapid removal of radioactive metals according to claim 1, characterized in that: In step S1, the particle size of the ball-milled material is less than 76 μm; the amount of the calcium compound and the magnesium compound is 25%-150% of the total mass of the clay mineral powder and the coal gangue powder, the amount of the magnesium compound is 10%-60% of the total mass of the calcium compound and the magnesium compound, and the amount of the coal gangue powder is 5%-30% of the total mass of the clay mineral and the coal gangue powder; The natural clay mineral powder includes one or more of attapulgite clay, illite, chlorite, montmorillonite, illite-montmorillonite, kaolinite, talc, quartz, calcite, amorphous hematite, feldspar, and mica; the mass fraction of carbon element in the coal gangue powder is 8%-15%.

3. The method for preparing a mineral-based adsorbent for rapid removal of radioactive metals according to claim 2, characterized in that: The calcium compound is at least one of calcium oxide, calcium hydroxide, calcium sulfate, calcium chloride, calcium carbonate, and calcium citrate; The magnesium compound is at least one of magnesium oxide, magnesium hydroxide, magnesium sulfate, magnesium chloride, magnesium carbonate, and magnesium citrate.

4. The method for preparing a mineral-based adsorbent for rapid removal of radioactive metals according to claim 1, characterized in that: In step S2, the amount of the boron compound is 30%-120% of the mass of the clay; The boron compound is at least one of boric acid, sodium tetraborate and sodium metaborate.

5. The method for preparing a mineral-based adsorbent for rapid removal of radioactive metals according to claim 1, characterized in that: In step S4, during calcination, the heating rate is 5-20°C / min.

6. The adsorbent prepared by the method for preparing a mineral-based adsorbent for rapidly removing radioactive metals according to any one of claims 1 to 5, characterized in that: The adsorbent is a porous silicate composite material containing silicon, magnesium, aluminum, boron, calcium and iron elements, and exists in the composite form of magnesium, aluminum or iron silicate and calcium borate.

7. Use of the adsorbent according to claim 6, characterized in that: Used to remove radioactive metal ions.

Citation Information

Patent Citations

  • High strength dried regenerative CO2 adsorbent taking coal gangue as carrier and preparation thereof

    CN101890331A

  • Method for preparing composite adsorbent by utilizing low-grade attapulgite clay

    CN104383873A